Search for causal relationship of macroeconomic veriables and testing the market effiency:an analytical approach to Turkish stock market - Öztürkkal, Belma (My University, 1996)
unknown
Keywords: Ekonomi; Finansman ekonomisi; Yatırım; Yatırımlar Türkiye